Theoretical Study of Palladium Membrane Reactor Performance During Propane Dehydrogenation Using CFD Method - Kamran Ghasemzadeh; Milad Mohammad Alinejad; Milad Ghahremani; Rahman Zeynali; Amin Pourgholi (Indonesian Journal of Chemistry, 2017)
This study presents a 2D-axisymmetric computational fluid dynamic (CFD) model to investigate the performance Pd membrane reactor (MR) during propane dehydrogenation process for hydrogen production. The proposed CFD model provided the local information of temperature and component concentration for the driving force analysis. After investigation of mesh independency of CFD model, the validation of CFD model results was carried out by other modeling data and a good agreement between CFD model results and theoretical data was achieved. Indeed, in the present model, a tubular reactor with length of 150 mm was considered, in which the Pt-Sn-K/Al2O3 as catalyst were filled in reaction zone. Hence, the effects of the important operating parameter (reaction temperature) on the performances of membrane reactor (MR) were studied in terms of propane conversion and hydrogen yield. The CFD results showed that the suggested MR system during propane dehydrogenation reaction presents higher performance with respect to once obtained in the conventional reactor (CR). In particular, by applying Pd membrane, was found that propane conversion can be increased from 41% to 49%. Moreover, the highest value of propane conversion (X = 91%) was reached in case of Pd-Ag MR. It was also established that the feed flow rate of the MR is to be the one of the most important factors defining efficiency of the propane dehydrogenation process.